Digital Translanguaging in Teaching Turath: Negotiating Tradition And Modernity At An Islamic University - Asriyyah, Kinnatul; Rochmaniyah, Eky Putri; Kusuma, Sofyan Dena; Haq, Muhammad A'inul; Nashrullah, Nashrullah; Amrulloh, Friendis Syani; Aziz, Imam Nur (Academia Publication, 2024)
The tension between preserving the linguistic sanctity of Turath (Islamic heritage) and accommodating the cognitive habits of digital natives represents a critical challenge in modern Islamic Higher Education. While traditional pedagogies often remain rigid, there is an urgent need to understand how digital interactions facilitate the negotiation of meaning between classical Arabic texts and contemporary student identities. Purpose: This study investigates how digital translanguaging practices function as a bridge between tradition and modernity within the context of Balaghah (Rhetoric) instruction. Method: Employing a virtual ethnographic case study at an Indonesian Islamic University, the research analyzed online interactions via WhatsApp and Zoom using a hybrid of Thematic Analysis and Computer-Mediated Discourse Analysis (CMDA). Key Findings: The results demonstrate that digital translanguaging serves as a strategic pedagogical resource rather than a linguistic deficiency. Four primary strategies emerged: (1) vernacularization for cognitive scaffolding, (2) trans-semiotizing through visual logic (emojis/memes), (3) the negotiation of authority via